Relationship between Student Engagement in Learning and Grade Point Average of Students - Kristiani, Rini; Oktafany; Setiawan, Gigih; Lisiswanti, Rika (CV. Jasa Sukses Abadi, 2024)
Student engagement in learning is a form of student participation in the learning process. There are three dimensions in student involvement, namely behavioral, emotional, and cognitive dimensions. This study aims to find the relationship between student engagement in learning and its dimensions on GPA in students of the Medical Education Study Program, Faculty of Medicine, Lampung University (PSPD FK Unila). This research design is descriptive analytic with a cross-sectional approach conducted on students of class 2022 PSPD FK Unila with the sampling technique is total sampling. The data collection process used the University Student Engagement Inventory (USEI) questionnaire along with demographic data for GPA. The research was conducted in October-November 2024. The analysis was conducted using the spearman test. The results showed that the level of student engagement The highest was in the medium + low category totaling 168 students (80.8%), the most dominant dimension in engagement was behavioral engagement, then cognitive, and the lowest was emotional. Most students' GPA is in the very satisfactory category (64.5%), followed by praise (20.2%), and the last is satisfactory (15.3%). There was a significant relationship between student engagement in learning and GPA (p value = 0.027, r = 0.155). Further analysis found that there was a relationship between behavioral engagement on GPA (p value = 0.014, r = 0.173) and cognitive engagement on GPA (p value = 0.021, r = 0.162), while emotional engagement showed no significant relationship on GPA (p value = 0.558). There is a significant relationship between student engagement in learning and GPA in FK Unila PSPD students. The dimensions that are significantly related to GPA are the dimensions of behavioral and cognitive engagement, while the emotional dimension does not show a significant relationship to student GPA.